A Hebrew Signature in a Latin Manuscript of Galen - Hartman, Dorota (Sefer yuḥasin ספר יוחסין | Review for the History of the Jews in South Italy | Rivista per la storia degli ebrei nell’Italia meridionale, 2013)
Una firma ebraica in un manoscritto latino di Galeno Il manoscritto VIII D 30 della Biblioteca Nazionale di Napoli, datato al tardo XIII - inizi del XIV secolo, contiene traduzioni latine di alcune opere di Galeno. L’importanza del codice è nota da tempo, ma sembra sinora sfuggita la presenza di una firma in ebraico posta al f. Iv, verso della prima pagina. La firma, che probabilmente indica un antico proprietario del manoscritto, si legge: יעקב בכ״ר שמשון Ya‘aqov ben kevod rabbî Šimšon, «Ya‘aqov figlio dell’onorato R. Šimšon». La firma è forse da porre in connessione con gli Anaṭoli, famiglia di traduttori, medici e filosofi attivi in Campania in età fridericiana, eventualmente trasferitasi a Benevento al tempo delle persecuzioni antiebraiche promosse dagli Angiò nell’ultimo quarto del XIII secolo. A Hebrew Signature in a Latin Manuscript of Galen Manuscript VIII D 30 in the National Library of Naples, unanimously dated to the late 13th – early 14th century, contains Latin versions of some of Galen’s medical treatises. While the importance of this manuscript is widely acknowledged, apparently the existence of a Hebrew signature in it has so far escaped notice. This signature can be seen in the middle of f. Iv, verso of the first leaf, which precedes f. 1r, where the first Galenic text begins. It is just a name, probably of the owner of the manuscript: יעקב בכ״ר שמשון Ya‘aqov ben kevod rabbî Šimšon, «Ya‘aqov son of the honoured R. Šimšon». Possibly the signature sheds some new light on the late stages of the Anaṭoli family, translators, physicians and philosophers, who may have moved from Naples to Benevento, in the Papal States, during the Angevine persecutions of the Jews, in the last quarter of the 13th century.